Cerebral autoregulation and symptoms of orthostatic hypotension in familial dysautonomia - Fuente Mora, Cristina (J Cereb Blood Flow Metab, 2016)
Familial dysautonomia is an inherited autonomic disorder with afferent baroreflex failure. We questioned why despite low blood pressure standing, surprisingly few familial dysautonomia patients complain of symptomatic hypotension or have syncope. Using transcranial Doppler ultrasonography of the middle cerebral artery, we measured flow velocity (mean, peak systolic, and diastolic), area under the curve, pulsatility index, and height of the dictrotic notch in 25 patients with familial dysautonomia and 15 controls. In patients, changing from sitting to a standing position, decreased BP from 124 ± 4/64 ± 3 to 82 ± 3/37 ± 2 mmHg (p < 0.0001, for both). Despite low BP, all patients denied orthostatic symptoms. Middle cerebral artery velocity fell minimally, and the magnitude of the reductions were similar to those observed in healthy controls, in whom BP upright did not fall. While standing, patients had a greater fall in cerebrovascular resistance (p < 0.0001), an increase in pulsatility (p < 0.0001), and a deepening of the dicrotic notch (p = 0.0010), findings all consistent with low cerebrovascular resistance. No significant changes occurred in controls. Patients born with baroreflex deafferentation retain the ability to buffer wide fluctuations in BP and auto-regulate cerebral blood flow. This explains how they can tolerate extremely low BPs standing that would otherwise induce syncope.